The discourse about upbringing and education of intellectually disabled children – analysis of selected Polish educational magazines which were printed from start of the XXth century till 1939 - Gandecka, Kamila (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
Development of revival and rehabilitation theory and practice in Polish pedagogical circles begins to increase intensively in the interwar period. The researchers from various scientific disciplines, particularly from disabled pedagogy, sociology of upbringing, child psychiatry and genetics, are getting involved in the case of the upbringing and education of different disabilities. The discussion concerns important tasks such as: creating separate types of schools for disabled students, inventing appropriate programmes of educating pedagogical and medical staff, sorting out the terminology in the range of diagnosis and the proper selection of children with intellectual dysfunction, upbringing social awareness of intellectual disability. These cases have been imprinted for good in the discussion about the upbringing and education of intellectually disabled children. It was conducted particularly by pedagogical magazines, which were printed from the start of the XXth century till 1939.
Keywords: upbringing; education; intellectual disability; pedagogic magazines